2021
DOI: 10.1108/jpmh-11-2020-0149
|View full text |Cite
|
Sign up to set email alerts
|

Depression and association with diet diversity score among adolescent (14-19) students of Jimma town high school, Jimma, southwest Ethiopia

Abstract: Purpose Dietary patterns are important for the physical and psychological development of adolescents. The purpose of this study is to determine magnitude and severity of depression and its relation with diet diversity score (DDS) among adolescent high school students. Design/methodology/approach A cross-sectional study was conducted among 546 adolescents selected from schools using multistage sampling technique. Dietary intakes were assessed using a 24-h dietary recall, and depression severity and prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A longitudinal study reported positive effects of greater food group diversity and maternal depressive symptoms [ 48 ]. Among adolescents, the proportion of moderate to severe and major depressive symptoms increased slightly as the DDS score decreased [ 49 ]. Dietary diversity in general, and diversity in certain food groups in particular, can reduce the risk of metabolism-related outcomes by improving the diversity of the gut microbiome [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study reported positive effects of greater food group diversity and maternal depressive symptoms [ 48 ]. Among adolescents, the proportion of moderate to severe and major depressive symptoms increased slightly as the DDS score decreased [ 49 ]. Dietary diversity in general, and diversity in certain food groups in particular, can reduce the risk of metabolism-related outcomes by improving the diversity of the gut microbiome [ 50 ].…”
Section: Discussionmentioning
confidence: 99%